Dectin-2-dependent host defense in mice infected with serotype 3 Streptococcus pneumoniae. (December 2016) - Akahori, Yukiko; Miyasaka, Tomomitsu; Toyama, Masahiko; Matsumoto, Ikumi; Miyahara, Anna; Zong, Tong; Ishii, Keiko; Kinjo, Yuki; Miyazaki, Yoshitsugu; Saijo, Shinobu; Iwakura, Yoichiro; Kawakami, Kazuyoshi
Abstract Background Streptococcus pneumoniae, a major causative bacterial pathogen of community-acquired pneumonia, possesses a thick polysaccharide capsule. Host defense against this bacterium is mediated by activation of innate immune cells that sense bacterial components. Recently, C-type lectin receptors (CLRs) have garnered much attention in elucidating the recognition mechanism of pathogen-derived polysaccharides. Methods In the present study, we first compared the clinical course and neutrophil accumulation in the lungs of Dectin-2 knock-out (KO) and wild type (WT) mice. Mice were infected intratracheally with a serotype 3 strain ofS. pneumoniae, andS. pneumoniae bacterial engulfment by neutrophils and inflammatory cytokine and anti-pneumococcal polysaccharide-specific IgG levels were evaluated in bronchoalveolar lavage fluid (BALF). We also examined the effect of Dectin-2 deficiency on interleukin (IL)-12 production by bone marrow-derived dendritic cells (BM-DCs) stimulated with the bacterial components. Results S. pneumonia- infected Dectin-2KO mice had a shorter survival time, larger bacterial burden and lower interferon gamma (IFN-γ) production in the lungs than WT mice. Although neutrophilic infiltration in the lungs was equivalent between Dectin-2KO mice and WT mice, S. pneumonia engulfment by neutrophils was attenuated in Dectin-2KO mice compared to WT mice. The anti-pneumococcal polysaccharide-specific IgG and IgG3 levels in BALF were lower in Dectin-2KO mice than in WT mice. When BM-DCs were stimulated withS. pneumoniae culture supernatant or its Concanavalin A (ConA)-bound fraction, IL-12 production was abrogated in Dectin-2KO mice compared to WT mice. Conclusions We demonstrated that Dectin-2 is intimately involved in the host defense against infection with a serotype 3 strain ofS. pneumoniae . Dectin-2-dependent IL-12 production may contribute to IFN-γ synthesis and subsequent production of serotype-specific anti-capsular polysaccharide IgG afterS. pneumoniae infection, which may promoteS. pneumoniae bacterial opsonization for engulfment.